RISET AKUNTANSI BERBASIS PASAR MODAL DI INDONESIA : KAJIAN TERHADAP KEBERMANFAATAN AKUNTANSI DALAM EMERGING MARKET - Utpala Rani (Riset Akuntansi Keuangan, 2016)
This study aimed to explore theadvance of market-based accounting research in Indonesia during 1990-2012. Focusing on the usefulness of accounting information, this study revealed that those researches mainly held to examine the applicability of theories used in previous foreign researches. Some studies shown different results, which could be interpreted that not all theories could be applied to explain the same phenomenon, especially concerning the specific characteristic of environment. This notion should be the researchers’ attention in order to make a more comprehensive conclusion about the phenomenon.